Baby boomers and generation xers : perceptions and expectations of current affairs and info-educational programmes - Lam, Siew Yen (2008)
This project examines the opinions of Baby Boomers and Generation Xers towards current affairs and info-educational programmes. Specifically, the project finds out whether Progamme Advisory Committee's recommendation is reflective of viewers' preferences. Factors that influenced Boomers and Xers' choice to watch such programmes are also discussed.